ANTIBIOTIC SUSCEPTIBILITY PATTERN OF ESCHERICHIA COLI ISOLATED FROM CHILDREN WITH URINARY TRACT INFECTION - OLI, YOGESH; BHANDARI, GANESH; BHANDARI, UPASHANA; BISTA, SUNITA; KUMAR BHATTARAI, AMRIT; KATUWAL, ARCHANA; BHANDARI, NETRA LAL (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: This work aimed to detect the antibiotic susceptibility pattern of Escherichia coli isolated from children, as it is the most predominant pathogen of urinary tract infection (UTI). Methods: About 530 urine samples were collected and tested using the modified Kirby–Bauer disk diffusion method to find the susceptibility pattern of isolated bacteria. Results: Out of a total of 530 samples, 114 (21.50%) showed significant growth. A total of 8 different types of bacteria were isolated from the growth of positive samples. Among the isolates, E. coli 66 (57.8%) was found to be the most predominant organism followed by Klebsiella pneumoniae 18(15.8%), Proteus spp. 10 (8.8%), Staphylococcus aureus 8 (7.0%), Acinetobacter spp. 4 (3.5%), CoNS 4 (3.5%), Enterobacter spp. 2 (1.8%), and Pseudomonas aeruginosa 2 (1.8%). In the present study, out of 66 E. coli, 37 (56.1%) were multidrug-resistant strain. E. coli showed 94.0% resistance to ceftriaxone followed by ceftazidime 86.5% and cefotaxime 70.3%. Imipenem (91.9%) followed by amikacin (89.2%) seems to be the effective drug against UTI causing E. coli in children. Conclusion: Multidrug resistance may possess difficulties with the choice of therapeutic options for the treatment of severe infections.